Local Culture Is Able To Bring In Foreign Tourists - Mariana Febrianti, R. Adjeng; Rizki Putra, Muhammad Nazhif (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
Pacitan is a coastal area with a small area of ​​rice fields, so many residents whose livelihoods are not farmers. The women spend more of their days and spare time with batik. The beauty of nature has inspired various decorations and motifs of Pacitan Batik, which are full of biological symbols. The typical Pacitan motifs are pace fruit or noni and sea coral. The classic batik made in Pacitan is now in danger of extinction because the batik artisans have entered an old age and regeneration has not yet matched the results. This research purposes to determine creativity effect and product innovation on customer satisfaction. The technique used in this study is multiple linear analysis with a sample of 90 respondents. The results in this study obtained a score of 54.2%, this score indicates that there is an influence between the variables of creativity and product innovation on customer satisfaction. This study is proposed to emphasize the importance of creativity and innovation skills in product development, especially in the batik industry in the city of Pacitan, East Java Province.